Critical impact of gate dielectric interfaces on the trap states and cumulative charge of high-performance organic thin field transistors. (1st March 2019) - Lin, Hui; Zhao, Wenqiang; Kong, Xiao; Li, Lijuan; Li, Yimeng; Kuang, Peng; Zhang, Yi; Zhang, Landan; Sun, Ming; Tao, Silu
Abstract: In the operation of OFETs, the electrical properties are strongly dependent on the merits of the constituting layers and the formed interfaces. Here we study the trap states variations at the interface between the organic semiconductor pentacene and polymer insulators. With ZrO2 dielectric modified by polymers and find a 10 × decrease in the density of trap states at the semiconductor/insulator interface, bring about the charge carrier mobility increase from 0.058 cm 2 /Vs to 0.335 cm 2 /Vs. In addition, when compare to the thicker films at the same applied gate voltage, the thinner film would lead to enhanced coupling capability and more charges cumulative cumulated at the channel region, which is pivotal for optimizing the performance of OFETs. The results prove that the property of the insulator layer could impact largely on the device performance.